2017
DOI: 10.1021/acs.energyfuels.7b01418
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ionic Liquids on the Viscoelastic Properties of Crude Oil Emulsions

Abstract: Thermochemical treatments are traditionally employed to perform the separation between the oil and water phases in the petroleum industry. The chemical agents have the function of reducing the barrier rigidity formed by natural surfactants present in the emulsion, thus favoring destabilization. The main objective of this study was to analyze the viscoelastic properties of samples composed of water and a crude oil with the addition of distinct ionic liquids. The methodology used to obtain the interfacial proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Series II copolymers only work as steric blocking layers among asphaltenes. 10,12,16 Aromatic pendant endows the copolymers strong adsorption to asphaltenes, and the aliphatic side chain gives the copolymers steric blocking ability. However, with only an aromatic pendant, copolymers can only adsorb on the surface of asphaltenes, but not hinder the aggregation of asphaltenes since there are no blocking pendants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Series II copolymers only work as steric blocking layers among asphaltenes. 10,12,16 Aromatic pendant endows the copolymers strong adsorption to asphaltenes, and the aliphatic side chain gives the copolymers steric blocking ability. However, with only an aromatic pendant, copolymers can only adsorb on the surface of asphaltenes, but not hinder the aggregation of asphaltenes since there are no blocking pendants.…”
Section: Resultsmentioning
confidence: 99%
“…To solve these problems, asphaltene dispersants have been developed and widely applied worldwide . Several approaches are available for stabilizing asphaltenes and preventing them from deposition, in which chemical dispersant is an effective one. A valid chemical dispersant generally contains an “anchoring” aromatic or polar group, which attaches itself to the surface of asphaltenes, and a “blocking” aliphatic group, which blocks asphaltenes from forming big clusters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some ionic liquids possess amphiphilic structure which enables them to have affinity to both water and oil phases [ 15 , 18 , 20 ]. The amphiphilic character may be in cation or anion part of ionic liquids structure.…”
Section: Ionic Liquid Demulsificationmentioning
confidence: 99%
“…Many research studies have been conducted for the application of ionic liquids in chemical demulsification processes, and it was reported that ionic liquids are reliable demulsifiers with high stability, even under harsh conditions (high temperature and high salinity) [ 19 ]. Ionic liquids are produced by a combination of different organic cations and organic or inorganic anions [ 20 ]. They are associated with unique characteristics such as thermal stability, non-flammability, recyclability, and low vapor pressure [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%